Rectify. The complete third season [videorecording (DVD)] - Young, Aden; Spencer, Abigail, 1981-; Clemens, Adelaide, 1989-; Smith-Cameron, J (Anchor Bay Entertainment, 2016)
It follows the life of Daniel Holden, who returns to his small hometown in Georgia after serving nineteen years on death row. Having spent his entire adult life waiting to die, Daniel must now try to find a way to cope with his past and forge a "normal" life with a future before him. Season three picks up on the very afternoon of Daniel's plea deal. Will the deal be accepted? Will Daniel be forced to leave town?